Workplace well-being in the London-Chinese business community. Issue 2 (3rd April 2017) - Bertotti, Marcello; Dan-Ogosi, Ifeoma Elizabeth; Rao, Mala
Abstract : Purpose: Workplace well-being is key to improving health and therefore productivity. Although the Chinese population and their influence on business in the UK are growing rapidly, little is known about the attitudes of Chinese employers and employees towards workplace well-being. The paper aims to discuss this issue. Design/methodology/approach: The authors conducted a qualitative study to explore the views of Chinese employees and employers in London and interviewed occupational health and workplace well-being experts. Findings: Employers' understanding of workplace well-being was limited, their approach was reactive rather than proactive. Contextual factors hampered most efforts towards workplace well-being. Employees reported that working conditions were generally poor with likely implications for employees' physical and mental health. Generational and migratory changes further complicate the scenario but potentially usher in positive change. Research limitations/implications: This study was conducted in a London area with a high density of Chinese businesses. The study nevertheless covered only a limited selection of business sectors. Caution may therefore be necessary in assuming the transferability of these findings to other parts of the UK. Practical implications: Chinese businesses are agreeable to being informed about and considering the business case for workplace well-being. Chinese workers need better working conditions, easier access to health services preferably delivered through Chinese-based networks of community and business associations which are trusted by both employers and employees. Originality/value: This study offers novel evidence on the attitude of Chinese employers and employees towards workplace well-being by comparing views from both groups. Chinese people face considerable health and mental health problems through their work environment, in contrast with conclusions from the Health Survey for England and Labour Force Survey.